Composing for acoustic robots: Instant synthesis for computer-controlled acoustic instruments through live coding and AI – A research conclusion - Drymonitis, Alexandros; Koutsomichalis, Marinos (My University, 2025)
This report presents the Postdoc research of the first author, titled Composing for Acoustic Robots: Instant Synthesis for Computer-Controlled Acoustic Instruments Through Live Coding and AI. This research focuses on instant composition for computer-controlled acoustic instruments through the LiveLily system. Inspired by earlier research by the first author, where music in the style of Bach was created live with the aid of AI, this research took this instant composition approach further, to include original music and combine that with robotic acoustic instruments. The research has been split in two parts, where in the first part a series of short instant compositions was created for a Yamaha Disklavier robotic piano and human performers, while the second part focused on a MIDI-controlled church organ. This split was an intentional method to enable us to test our system in a concert setting and fine tune it according to how it performed, so we could get better results in the second concert. The results of this research are original instant compositions for these two instruments, part of which we present in this paper. Through this process, we developed a system for creating traditional Western-music scores for computer-controlled acoustic instruments live, through live coding and AI, as a way to create instant compositions while maintaining a steady pase for the music content generation.
Keywords: Live Scoring; Robotic Instruments; Artificial Intelligence; Instant Composition; Instant Synthesis; Live Coding